2001
DOI: 10.1016/s0735-1097(01)01477-2
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus prevents ischemic preconditioning in patients with a first acute anterior wall myocardial infarction

Abstract: Prodromal angina limited infarct size, enhanced recovery of LV function and improved survival in non-diabetic patients with AMI. However, such beneficial effects of prodromal angina were not observed in diabetic patients, suggesting that diabetes might prevent ischemic preconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
2
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(113 citation statements)
references
References 23 publications
4
100
2
7
Order By: Relevance
“…First, despite inclusion and exclusion criteria in DELTA MI that were designed to define a very specific, homogeneous patient population, factors that significantly influence biomarker end points (including total ischemia time before reperfusion, diabetes mellitus, prodromal angina before presentation, and collaterals to the LAD distribution) varied substantially among active study drug versus concurrent placebo across dosing cohorts and influenced the evaluation of drug activity with the biomarker results. [12][13][14][15][16][17][18][19] Second, we observed a wide variability in the interquartile ranges of the quantitative biomarker results because of the small sample sizes of the dosing cohorts, and this variability influenced the statistical comparisons between active study drug versus concurrent placebo within dosing cohorts and prevented definitive conclusions on the impact of active study drug. Finally, we demonstrated consistent but nonsignificant improvements with active study drug with biomarkers collected during the first 24 to 36 hours such as ST recovery and CK-MB AUC values.…”
Section: Use Of Biomarkers Of Reperfusion Successmentioning
confidence: 92%
“…First, despite inclusion and exclusion criteria in DELTA MI that were designed to define a very specific, homogeneous patient population, factors that significantly influence biomarker end points (including total ischemia time before reperfusion, diabetes mellitus, prodromal angina before presentation, and collaterals to the LAD distribution) varied substantially among active study drug versus concurrent placebo across dosing cohorts and influenced the evaluation of drug activity with the biomarker results. [12][13][14][15][16][17][18][19] Second, we observed a wide variability in the interquartile ranges of the quantitative biomarker results because of the small sample sizes of the dosing cohorts, and this variability influenced the statistical comparisons between active study drug versus concurrent placebo within dosing cohorts and prevented definitive conclusions on the impact of active study drug. Finally, we demonstrated consistent but nonsignificant improvements with active study drug with biomarkers collected during the first 24 to 36 hours such as ST recovery and CK-MB AUC values.…”
Section: Use Of Biomarkers Of Reperfusion Successmentioning
confidence: 92%
“…However, Cleveland et al reported that human right atrial trabeculae extracts with insulin-treated diabetes were responsive to an IP stimulus whereas tissues subjected to long term treatment with oral antidiabetic agents, were not (116). Furthermore, the beneficial effects of prodromal angina (limited infarct size, enhanced recovery of LV function and improved survival) were not observed in non-insulin-treated diabetic patients (117). Treatment of type II diabetics with glibenclamide blocked the warm up phenomenon (118) and prevented the improvement of hemodynamic variables normally observed following the first balloon inflation during PTCA (119).…”
Section: Ip and The Diseased Heartmentioning
confidence: 99%
“…(57)(58)(59)(60) , enquanto outros avaliaram desfechos clínicos (17,18) . Entretanto, apesar de seus resultados consistentes, a informação do presente estudo é contrária aos achados de Lee e colaboradores (17) e Ishihara e colaboradores (18) , que também estudaram o precondicionamento isquêmico em humanos.…”
Section: Discussionunclassified
“…Entretanto, acredita-se que fatores miocárdicos também estejam alterados nestes pacientes. Alguns trabalhos (17,18) sugerem que a resposta miocárdica a insultos isquêmicos em portadores de diabetes mellitus esteja alterada, predispondo a maior dano miocárdico e a maior suscetibilidade a complicações isquêmicas. Uma vez que o prognóstico cardiovascular encontra-se relacionado ao tamanho da área infartada após um evento agudo coronariano, a resposta miocárdica ao insulto isquêmico tem sido foco de estudos, especialmente em modelos experimentais e em pacientes com diabetes mellitus, visando à melhor compreensão dos fenômenos, menor lesão miocárdica e, assim, melhor prognóstico.…”
Section: Dados Internacionais De Catalogação Na Publicação (Cip)unclassified
See 1 more Smart Citation